Tourism industry in the new member states. Key countries and destinations - Ana Maria-Irina (Management şi Marketing, 2018)
This paper provides an examination of tourism in the New Member States of the European Union in the period 2007-2015, assessing the importance of tourism for the New Member States economy and the factors that might affect this industry. Considerable research has been devoted to tourism in the developed countries from Europe, but rather less attention has been paid to tourism in the Central-Eastern Europe, the New Member States region. In this regard, the paper will start with an overview of the current state of the literature on this topic, section that precedes a presentation of European bodies and policies in the travel and tourism field. Time series will be analyzed in order to identify the key countries for tourism in the region, according to the number of international arrivals, number of international overnight stays and exports in trade. Tourism contribution and importance for the economy, key destinations in the region, EU and state-level policies in the tourism sector, as well as main challenges and opportunities in the tourism sector will be addressed, focusing on the three key countries identified, Poland, Czech Republic and Croatia, that offer tourists unique, traditional experiences, focusing on niche markets, rather than on mass-market tourism.